2020
DOI: 10.18311/jbc/2020/22833
|View full text |Cite
|
Sign up to set email alerts
|

Fruit fly management in Nepal: A case from plant clinic

Abstract: Fruit fly is one of the important insect pests of horticultural crops, both fruits and vegetables. After aphids, fruit fly was reported as a major insect problem in the plant clinic sessions from September 2013 to July 2016 in Nepal. The groups of horticultural crops most affected by fruit flies were cucurbitaceous vegetables, i.e. 79% of all fruit fly queries (bitter gourd, bottle gourd, chayote, cucumber, pumpkin, snake gourd, sponge gourd and squash) followed by fruits 14% (guava, sweet orange, mandarin, ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 2 publications
1
9
0
Order By: Relevance
“…This deduces that plant health clinic training services had statistically significant influence on potato production in Molo Sub-County. These findings concur with those of Adhikari et al (2020) who found out that frequency of receiving plant health clinic training services result in skills and knowledge enhancement which is likely to increase uptake of recommendations on how to handle issues such as pests and diseases therefore the likelihood of crop production improvement in Nepal. It is expected that since plant health clinic training services offer the type of training services such as management of pests and diseases and production practices farmers which can maximize production through use of acquired skills and knowledge therefore increase yields.…”
Section: As Shown Insupporting
confidence: 90%
“…This deduces that plant health clinic training services had statistically significant influence on potato production in Molo Sub-County. These findings concur with those of Adhikari et al (2020) who found out that frequency of receiving plant health clinic training services result in skills and knowledge enhancement which is likely to increase uptake of recommendations on how to handle issues such as pests and diseases therefore the likelihood of crop production improvement in Nepal. It is expected that since plant health clinic training services offer the type of training services such as management of pests and diseases and production practices farmers which can maximize production through use of acquired skills and knowledge therefore increase yields.…”
Section: As Shown Insupporting
confidence: 90%
“…The seeds were directly sown on the experimental and control trial plots of 100 m 2 each during early March. Bitter gourd was selected for the study because it is commercially grown and widely consumed, and it is highly affected by fruit fly infestation compared to other horticultural crops like fruits and solanaceous vegetables [ 52 ]. Altogether, 16 lead farmers from eight sites were selected based on their willingness to participate in the research on jholmal application.…”
Section: Methodsmentioning
confidence: 99%
“…Ten different management measures such as sanitation, trapping adult using para-pheromone lures, chemical insecticides, botanicals, cultural measures, exclusion through bagging and netting, food lure/protein bait, bio-pesticides, post-harvest treatments and sterile insect technique mentioned in fruit fly management (Adhikari, Joshi, Thapa, Pandit, & Sharma, 2020c), whereas, only seven management measures were recommended by the extension advisory service providers in Nepal (Adhikari, Joshi, Thapa, Pandit, & Sharma, 2020c). According to Dhillon, Singh, Naresh, & Sharma (2005), fruit fly management options such as sanitation of infested fruits, bagging of fruits, protein bait application, use of para-pheromone traps and chemical insecticides were recommended practices for the growers.…”
Section: Management Practicesmentioning
confidence: 99%
“…B. minax infestation rates of 50 to 100% could be reduced to less than 1% with the proper sanitation procedures (Wang & Zhang, 2009;Wang & Luo, 1995;Peng, 1990). Reported other measures of cultural methods were soil treatment/tillage, removal of host plants, crop rotation, clean cultivation, weeding, pruning, conservation of natural enemies, early harvesting, bait traps and repellent crops (Adhikari, Joshi, Thapa, Pandit, & Sharma, 2020c). In Bhutan, cultural measures including soil tillage, and also natural predation (birds eating pupae) appeared to have a role in decreasing the number of pupae in orchards (Dorji, Mahat, & Loday, 2010).…”
Section: Management Practicesmentioning
confidence: 99%
See 1 more Smart Citation